From Klinefelter Syndrome to High Grade Aneuploidies: Expanding the Gene-dosage Effect of Supernumerary X Chromosomes - Spaziani, Matteo; Carlomagno, Francesco; Tarantino, Chiara; Angelini, Francesco; Paparella, Roberto; Tarani, Luigi; Putotto, Carolina; Badagliacca, Roberto; Pozza, Carlotta; Isidori, Andrea M; Gianfrilli, Daniele (The journal of clinical endocrinology and metabolism, 2024)
Abstract Objective High-grade aneuploidies of X and Y sex chromosomes (HGAs) are exceedingly rare and complex conditions. We aimed to investigate the effect of supernumerary X chromosomes (extra-Xs) on the clinical, hormonal, metabolic, and echocardiographic features of patients with HGAs. Design and Methods In a cross-sectional study, we compared 23 subjects with HGAs and 46 age-matched subjects with 47,XXY Klinefelter syndrome (KS), according to the number of extra-Xs: two (47,XXY and 48,XXYY), three (48,XXXY and 49,XXXYY), or four supernumerary Xs (49,XXXXY). A second cohort consisting of 46 pubertal stage-matched KS subjects was employed for validation. Clinical, hormonal, metabolic and ultrasonographic parameters were collected and analyzed. Results The increase in the number of extra-Xs was associated with a progressive adverse effect on height, pubertal development, testicular volume and function, adrenal steroidogenesis, and thyroid function. A progressive linear increase in ACTH and a decrease in cortisol/ACTH ratios were found. Weight and body mass index, Sertoli cell function, lipid profile, and glucose tolerance post-oral glucose tolerance test were all worse in the HGA cohort compared to KS. Cardiac evaluation revealed a linear association with reduced left and right end-diastolic diameters and reduced ejection fraction. Conclusion The increase in the number of extra-Xs is associated with a “dose-dependent” progressive impairment in steroid producing glands, thyroid function, cardiac structure, and performance.